A case of disseminated intravascular coagulation after two-jaw surgery. Issue 5 (September 2018) - Yasuda, Arisa; Sato, Hitoshi; Inada, Takanobu; Abe, Yuzo; Tanaka, Motohiro; Kurihara, Mai; Shirota, Tatsuo
Abstract: Disseminated intravascular coagulation (DIC) is a serious condition that causes persistent widespread coagulation activation in the presence of underlying disease. Most patients who undergo orthognathic surgery are young and have no underlying disease. Therefore, serious postoperative complications such as DIC rarely arise. We describe a patient with DIC that developed after two-jaw surgery in the absence of underlying disease. A 31-year-old man was referred to our hospital with a chief complaint of an occlusal abnormality. He had no underlying disease and his preoperative laboratory findings were unremarkable. The patient provided presurgical, written, informed consent to orthognathic surgery including Le Fort I osteotomy and bilateral sagittal split ramus osteotomy. Perioperative findings and events were also unremarkable. The surgical duration was 4 h and 31 min. Blood loss was 435 mL and he was transfused with 400 mL of hemodiluted autologous blood. The patient developed obvious facial swelling and ecchymosis from the infraorbital area to the cheek in both sides of the face on postoperative day (POD) 5. Blood findings on POD 6 were as follows: RBC, 365 × 10 4 /μL; WBC, 9, 200/μL; PLT, 0.3 × 10 4 /μL; FDP, 21.25 μg/mL; Fibrinogen, 501 mg/dL; and D-dimer, 10.67 μg/mL. Treatment for early symptomatic improvement was started, since these findings met several criteria for diagnosis of DIC. Blood parameters improved (PLT, 6.5 × 10 4 /μL; FDP, 11.05 μg/mL; D-dimer, 5.24 μg/mL) one day after the intravenous administration of prednisolone (60 mg) and transfusion with 10 units of platelet concentrate. Thereafter, the clinical course was uneventful.